Front Cover: Magnesium Oxide‐Catalyzed Conversion of Chitin to Lactic Acid (ChemistryOpen 3/2021) - Kun‐asa, Kodchakon (ChemistryOpen, 2021)
The Front Cover shows the conversion of chitin, which is generated by food processing, into lactic acid with catalysis by magnesium oxides. Although chitin, a main component of the shells of crustaceans, can be converted to valuable products by means of homogeneous catalysis, most of the chitin is treated as industrial waste because use of homogeneous catalysts is compromised by difficulties associated with product separation from the catalysts and the recyclability of the catalysts. Thus, a method for converting chitin to useful chemicals, such as lactic acid, by using solid catalysts would be beneficial. Magnesium oxide catalysts can be reused twice without loss of activity. More information can be found in the Full Paper by Kodchakon Kun‐asa et al.[Image: see text]